2018
DOI: 10.1002/sej.1296
|View full text |Cite
|
Sign up to set email alerts
|

Turning strategic network resources into performance: The mediating role of network identity of small‐ and medium‐sized enterprises

Abstract: Research Summary: This article examines the relationship between strategic network resources; the network identity (i.e., the selfperceived attractiveness as a partner based on the firm's existing and prior relationships); and firm performance among established smalland medium-sized enterprises (SMEs). We test our hypotheses within the sample of 199 internationalized SMEs in Finland. We contribute to the discussion on the performance effects of network resources among small firms by demonstrating that: (a) net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 167 publications
(241 reference statements)
1
42
0
1
Order By: Relevance
“…This is not surprising with entrepreneurs in emerging markets who strive to maintain the confidentiality and secrecy of their operations and performance. Nevertheless, a self-reported multi-item subjective performance measure for small firms has been consistently shown to be highly correlated with and provide similar effect sizes to archival objective measures (Partanen et al , 2020; Stam et al , 2014).…”
Section: Methodsmentioning
confidence: 95%
“…This is not surprising with entrepreneurs in emerging markets who strive to maintain the confidentiality and secrecy of their operations and performance. Nevertheless, a self-reported multi-item subjective performance measure for small firms has been consistently shown to be highly correlated with and provide similar effect sizes to archival objective measures (Partanen et al , 2020; Stam et al , 2014).…”
Section: Methodsmentioning
confidence: 95%
“…This way SMEs can find new opportunities. Networks supply access to quality information, especially tacit knowledge for innovation when trust is established between the actors (Acheampong & Hinson, 2019;Partanen et al, 2020). However, the value of knowledge available through these networks depends on the SME's absorptive capacity (Zhai et al, 2018;Limaj & Bernroider, 2019 All of these studies showed that an SME's network contributes to enabling its access to resources.…”
Section: Innovation and Smesmentioning
confidence: 99%
“…Moreover, SMEs often operate in niche markets and risk the collapse of their business model if they fail to react to environmental changes that call for a major strategy revision or a product portfolio adaptation (Chan et al 2019). Being able to establish adequate partnerships, to dynamically adapt ones' capabilities, and to develop agile supply chains seem to be effective strategies to meet these challenges (Rodríguez-Serrano and Martín-Armario 2017; Partanen et al 2018). SMEs even use such partnerships as strategic instruments to overcome their resource constraints (Findikoglu and Watson-Manheim 2015).…”
Section: Cooperative Relationships and Organizational Agilitymentioning
confidence: 99%
“…Earlier research has endorsed these resource-driven motivations for SMEs' cooperative behavior and has suggested that SMEs benefit from cooperation in terms of profit growth (Partanen et al 2018), international performance (Ripollés and Blesa 2019), and innovation (Gnyawali and Park 2009). Since they often lack formal internal R&D activities, SMEs depend even more on access to external knowledge to accumulate technological or managerial knowledge and to be successful at innovation than large, diversified, multi-establishment firms (Rothwell and Dodgson 1991;Acs et al 1994;Smallbone et al 1999;Payne et al 2009;Chun and Mun 2012;Radicic et al 2018).…”
Section: Cooperative Relationships and Organizational Agilitymentioning
confidence: 99%